THE LOCALIZATION OF AUSTRALIA ANTIGEN BY IMMUNOFLUORESCENCE - Coyne(Zavatone), Veronica E. (The Rockefeller University Press, 1970)
We have studied the localization of Australia antigen, a particulate substance associated with hepatitis, by means of the fluorescent antibody technique. Preparations were made from 61 liver biopsy specimens taken from patients with infectious hepatitis, serum hepatitis, and a variety of other diseases. When tested with fluorescein-conjugated rabbit anti-Au(1) antisera all 26 patients who had Au(1) in their serum had specific fluorescence in their liver cells. The fluorescence appeared in three forms: as discrete particles within the nucleus, diffuse fluorescence of the entire nucleus, and fluorescence of the nuclear rim. Occasionally there were also fluorescent particles in the cytoplasm. Other specimens were tested with the fluorescent antibody including a variety of human tissues, buffy coat smears, peripheral lymphocyte cultures, and cells obtained from bile and duodenal drainage. Among these specimens, fluorescence was found in the cytoplasm of a few cells in the bone marrow of two patients with hepatitis and Au(1) in their serum, and in the liver, spleen, mesentery, and testis of one patient with leukemia, chronic hepatitis, and Au(1) in his serum. We have shown that the presence of fluorescent particles in the liver cells is strongly associated with the presence of Au(1) in the serum and the diagnosis of viral hepatitis. We believe that this study adds support to the hypothesis that Australia antigen is an antigenic determinant of a virus capable of causing hepatitis.